ncome Tax and VAT Issues Concerning Leases after IFRS 16 Convergence in Indonesia - Prianto Budi Saptono Mail (Ikatan Akuntan Indonesia, 2021)
This study analyzes income tax and value-added tax (VAT) issues on lease transactions after IFRS 16 convergence in Indonesia into PSAK 73. The data collection is through in-depth interviews and literature review. We interviewed informants selected purposively. We also used secondary data from literature studies to enrich the analysis. This study concludes that the tax authorities need to make tax policies that can provide legal certainty. The new tax regulation needs to accommodate a more precise direction of the policy. Among the three available options, this study favors realization taxation as a more appropriate option for Indonesia’s current situation, other than mark-to-market or hybrid taxation. To narrow the practical gap between accounting and tax, this study recommends that tax authorities initiate a discussion with relevant stakeholders to prevent potential tax disputes in the coming years. Tax authorities need to notice some issues with withholding tax when the lessee records interest expenses as well as transfer/delivery issues causing VAT payable when the lessee recognizes a right-of -use asset.